Signos de los tiempos: sentido y vigencia de una forma de proceder teológicamente (2018)
The article offers reflections that emphasize the validity of the proceeding that is condensed in the symbolic, biblical and pastoral expression of the signs of the times. First, it proposes central ideas from the work of Christoph Theobald about the principle of pastorality that he identifies as the great legacy of the Council. Second, the text refers to the methodological debate that arose in the drafting stage of Gaudium et spes. Particular attention to the arguments shows that an important transformation in theological methodology was taking place. Finally, the paper reflects on the relevance of this way of proceeding towards the current cultural conditions of humanity characterized by cultural pluralism and religious diversity.